(untitled) (World Bulletin of Social Sciences, 2023)
This research seeks to determine the dimensions of (ITG) that could reduce CAIS risks in Iraq industrial firms. This research used a snowball sample technique to collect data from 291 employees worked in Iraq industrial firms. The results showed that all dimensions of (ITG) (Firm & Planning, Acquire & Implementation, Delivery & Support, Monitoring & Evaluation, Guidance & Control) have an impact on the decrease of CAIS risks significantly and positively